The Role of Adults in “Youth Led” Climate Groups: Enabling Empowerment - Elsen, Felix; Ord, Jon (Frontiers in Political Science, 2021)
This research explores young people's attitudes toward adult involvement within “youth led” youth climate groups. Young people were acutely aware of their marginalization and overall, there was a consensus that adults played a useful role as a resource, as experienced adult activists possessed knowledge that they lacked, or in offering practical support on legal issues or liaising with the police. The attitudes of young people to adult involvement is at times paradoxical in that whilst they were aware of its necessity, adults altered the dynamics of the groups, as there was a “power gap” and that adults' views could take precedence. As a result, on some occasions the young people parted ways from the adults. A continual theme from the research was that young people's involvement in “youth climate groups” gave them a sense of empowerment and they were much more aware of how to effect change, and to some extent they did need the support of adults in this process, often due to their structural disempowerment. The findings suggest that adult involvement was most successful when adults were committed to empowering young people and the researchers suggest that Kirshner's model of “cycles of fading” is a useful framework for adult involvement.